A Comparative Study on Microscopic Characteristics of Volcanic Reservoirs in the Carboniferous Kalagang and Haerjiawu Formations in the Santanghu Basin, China - Wang, Weiming; La, Weihao; Fan, Tanguang; Xu, Xiongfei; Liu, Yingnan; Lv, Qixia (Frontiers in Earth Science, 2021)
Self-jetting high-yield oil flow was obtained from Ma 67 and Ma 36 wells drilled in the volcanic reservoirs of the Haerjiawu Formation in the Santanghu Basin, China. This has shifted the prospectors’ attention to the Haerjiawu Formation from the Kalagang Formation, which is generally considered to have favorable physical properties. To further explain the geological reasons why oil flow can jet itself from the volcanic rocks in the Haerjiawu Formation with poor physical properties, this study carries out a systematic comparison on the microscopic pore structures of volcanic rocks through unconventional tests such as low-temperature nitrogen adsorption, high-pressure mercury injection, and constant-rate mercury injection based on the analyses of physical properties and minerals. The results obtained are as follows. The volcanic rocks of the Kalagang Formation have relatively high pore permeability. However, their micropores have a wide distribution range of pore size and feature highly meandering structures and strong heterogeneity. Meanwhile, small pore throats connect large pores in the volcanic rocks, resulting in a relatively high pore/throat ratio. All these are conducive to the occurrence of tight oil and gas but unfavorable for the flow of oil and gas. The volcanic rocks in the Haerjiawu Formation have relatively low volcanic permeability. However, small pores connect large pore throats in the volcanic rocks; thus, leading to a relatively low pore/throat ratio. Meanwhile, the volcanic rocks feature low meandering structures, strong homogeneity, and high connectivity. All these are favorable for the formation of tight oil and gas reservoirs. These assessment results also indicate that the assessment indices of tight volcanic reservoirs should not only include porosity and permeability. Instead, more attention should be paid to the microscopic pore structures, and it is necessary to analyze the charging and flow of tight oil from the configuration of pores and pore throats. This study not only explains the geological factors of the wells with self-jetting high-yield oil flow in the Haerjiawu Formation from the perspective of microscopic pore structures but also provides a new idea and comparison method for the assessment of tight reservoirs in other areas.